Audio Podcast and Video Practical for Short and Long-Term Memory Student - Nuki Dhamayanti (Universitas PGRI Semarang, 2023)
Listening items on the Marlins Test are more varied with various nationality accents. Seafarers' listening ability can be improved by listening to different language accents. This research used here is a quasi-experimental research design. The sampling method used for Non-Probability Sampling. Based on the results of the analysis and discussion, the following conclusions are obtained: there is no significant difference between Using Audio Podcast and Video Practical Training (Students with Short Term and Long-Term Memory) groups; there is no significant difference between Student Short Term Memory – Student Long Term Memory; there is a significant difference between the two Audio Podcast groups (Student Short Term Memory – Student Long Term Memory); there is no significant difference between the two Video Practical Training groups (Student Short Term Memory – Student Long Term Memory). The use of audio podcasts in teaching listening needs to be increased because it is effective for students inside and outside the classroom. The existence of podcasting contributes to helping teaching and learning activities run well. That is because listening comprehension becomes a complex process to understand spoken language in English Foreign Language learners. The use of audio podcasts in achieving listening skills in teaching activities needs to be investigated further. Literature research using the systematic review method to determine the effectiveness of audio podcasts in teaching listening at all levels of students needs to be studied further. The use of audio podcasts in teaching listening needs to be increased because it is effective for students inside and outside the classroom.